Steady state performance of anaerobic degradation of Palm Oil Mill Effluent (POME) at various Hydraulic Retention Time (HRT) - Yee, Shian Wong; Ong, Soon An; Tjoon, Tow Teng (Universiti Sains Malaysia (USM), 2011)
Organized by Universiti Sains Malaysia (USM), 2nd - 4th June 2010 at Penang, Malaysia.